Application Of Supplementary Penalty As A Substitute For Money In Cases Of Corruption Criminal Proceedings - Muammar, Muammar; Meldandy, Maulana (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
Abstract The determination of additional punishment in the form of "replacement money" should ideally be equal or balanced with state financial losses as a result of criminal acts of corruption. Interesting in the decision of the Semarang District Court Number: 32/Pid.Sus/2012/PN.Tipikor.smg there is an unequal determination of "replacement money" when compared to state financial losses caused by criminal acts of corruption committed by the defendant in the "Budget" corruption case. Maintenance of Motorized Service Vehicles by the Chairperson of the Regional Legislative Council of Grobogan Regency for the 2009-2014 period”. This type of normative legal research with a normative juridical approach examines library materials in the form of books, magazines and legislation that correlates with the discussion of the problem. Regarding the legality of additional criminal charges in the form of substitute money in corruption cases, it is stated in Article 18 paragraph (1) letter b of Law no. 31 of 1999 concerning the Crime of Corruption, namely "payment of compensation as much as possible equal to the property obtained from the crime of corruption". The judge's consideration in the decision above is concluded to be less relevant if it is associated with additional penalties in the verdict in the form of replacement money. Keywords: corruption; replacement money; supplementary penalty